Wear-resistant NbMoTaWTi high entropy alloy coating prepared by laser cladding on TC4 titanium alloy. (April 2023) - Ren, Z.Y.; Hu, Y.L.; Tong, Yonggang; Cai, Z.H.; Liu, Jian; Wang, H.D.; Liao, J.Z.; Xu, S.; Li, L.K.
Abstract: To improve the microhardness and wear resistance of TC4 alloy, NbMoTaWTi high-entropy alloy coating was fabricated on the surface of TC4 alloy by laser cladding. The coating exhibited a single BCC phase. The top microstructure of the coating was dominated by fine dendrites while the bottom region near the interface was composed of petal-like coarse dendrites. The microhardness of the coating reached to 600 HV, which was 72% higher than that of the substrate. The wear surface of the coating was flat and adhered to some of abrasive material. The specific wear rate of the coating was 1.37 × 10 −4 mm 3 /(N∙m), which decreased by 121.9% than that of the substrate. The primary wear mechanisms of the coating were oxidative wear and adhesive wear.